Microglia and monocyte-derived macrophages: functionally distinct populations that act in concert in CNS plasticity and repair - London, Anat; Cohen, Merav; Schwartz, Michal (Frontiers in Cellular Neuroscience, 2013)
Functional macrophage heterogeneity is recognized outside the central nervous system (CNS), where alternatively-activated macrophages can perform immune-resolving functions. Such functional heterogeneity was largely ignored in the CNS, with respect to the resident microglia and the myeloid-derived cells recruited from the blood following injury or disease, previously defined as blood-derived microglia; both were indistinguishably perceived detrimental. Our studies have led us to view the myeloid-derived infiltrating cells as functionally distinct from the resident microglia, and accordingly, to name them monocyte-derived macrophages (mo-MΦ). Although microglia perform various maintenance and protective roles, under certain conditions when they can no longer provide protection, mo-MΦ are recruited to the damaged CNS; there, they act not as microglial replacements but rather assistant cells, providing activities that cannot be timely performed by the resident cells. Here, we focus on the functional heterogeneity of microglia/mo-MΦ, emphasizing that, as opposed to the mo-MΦ, microglia often fail to timely acquire the phenotype essential for CNS repair.